2010
DOI: 10.1007/s00705-010-0753-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the nonstructural protein NS80 of grass carp reovirus

Abstract: Nonstructural proteins of members of the family Reoviridae are believed to play significant roles in the virus replication cycle. Phylogenetic analyses indicate that the nonstructural protein NS80 of grass carp reovirus, encoded by a gene of Segment 4 (S4), is a primary determinant that is related to the formation of viroplasmic inclusion bodies (VIB), where viral replication and assembly are thought to occur. To understand the role of the NS80 protein in viral replication, an initial investigation of NS80 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 28 publications
4
39
0
Order By: Relevance
“…Similarly, a shorter fragment with NS80 expression has also been found in GCRV-infected cells (Fan et al, 2009b;Fan et al, 2010;Shao et al, 2013;Yan et al, 2015). These results suggest that NS80 presents different forms or structural conformations in infected cells to regulate viral replication and assembly at different life cycle stages.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Similarly, a shorter fragment with NS80 expression has also been found in GCRV-infected cells (Fan et al, 2009b;Fan et al, 2010;Shao et al, 2013;Yan et al, 2015). These results suggest that NS80 presents different forms or structural conformations in infected cells to regulate viral replication and assembly at different life cycle stages.…”
Section: Introductionmentioning
confidence: 65%
“…VP5 and VP7 make up the outer capsid required for viral entry into host cells during infection . In addition, the nonstructural proteins are involved in the viral replication cycle (Fan et al, 2009a;Fan et al, 2010;Cai et al, 2011;Shao et al, 2013;Yan et al, 2015). Phylogenetic and three-dimensional structural analyses have revealed that there is a close evolutionary relationship between aquareoviruses and orthoreoviruses, including mammalian orthoreoviruses (MRV) and avian reoviruses (ARV) (Shaw et al, 1996;Attoui et al, 2002;Fang et al, 2005;Cheng et al, 2008;Cheng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The grass carp is the most economically important fish species cultivated in China, with an annual production of more than 3.6 million metric tons. Frequent outbreaks of hemorrhagic disease resulting from GCRV infection have resulted in significant economic losses in the grass carp cultivation industry [2,3]. GCRV is a dsRNA virus with a double-layered protein capsid, while the GCRV genome comprises 11 dsRNA genomic fragments encoding 12 viral proteins [4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on analyses of the AqRV-C genome and of 3D structure, the properties of the viral structural proteins have been well characterized (Cheng et al, 2008(Cheng et al, , 2010Zhang et al, 2010). The major nonstructural protein NS80, the analogue of the mNS protein in mammalian orthoreoviruses (MRVs) and avian reoviruses (ARVs), which is encoded by the S4 genome segment, has been demonstrated to be involved in viral factory or viral inclusion formation during infection (Cai et al, 2011;Fan et al, 2010). Recently, we demonstrated that NS80 can recruit the minor core protein VP4 and nonstructural protein NS38 to its inclusions, and the C-terminal domain of NS80 is the primary driving force for inclusion formation .…”
mentioning
confidence: 99%